Strategi Perusahaan Retail (Transmart Rungkut Surabaya) Dalam Menambah Peluang Usaha Bagi UMKM - Fitria, Laila Romadhoni Ayu; Andarini, Sonja (Universitas Gajah Putih, Indonesia, 2023)
In the current era of globalization, there is a lot of competition among business people, especially in the MSME business (Micro, Small and Medium Enterprises). MSME is an activity that is simple, both in terms of production patterns, organization, workforce and technology. MSMEs have a crucial role in economic growth in Indonesia. Even so, the role of MSMEs has not been able to realize economic growth because there are still many constraints from several aspects, such as not being able to compete with products from large companies. The MSME business competitors are not only from within the country but also from abroad. This study aims to determine the strategy of Transmart Rungkut Surabaya in increasing business opportunities for MSMEs. The research method used is descriptive method with a qualitative approach such as making observations and conducting interviews with Transmart. The results of this study are that MSME business people can be helped in terms of increasing sales / income through collaboration between Transmart Rungkut Surabaya